All Sustainable Development Goals Support Good Health and Well-Being - Weeks, Bill; Weinstein, James; Lavista Ferres, Juan M. (International Journal of Public Health, 2023)
Margaret Mead said that the first sign of civilization was a broken femur that had been healed. Humanity’s willingness and ability to care for one another defines civilization; without that inclination, we are considered animals. Since civilization began, humanity has become more sophisticated in caring for itself. Now, we attempt to fix broken hearts, psyches, and appendices as well as femurs. Although we have different ways of funding those fixes, there is a general global sense that health and healthcare are fundamental rights. In the United States, our founding fathers declared a right to life, liberty, and the pursuit of happiness: while life and health may not be equivalent, the absence of the former eradicates the latter, and the absence of the latter likely compromises liberty and the pursuit of happiness. In civilization’s evolutionary development, humanity has done a lot of harm to its members and the planet. To redress that harm, in 2015, the United Nations General Assembly (UNGA) defined 17 sustainable development goals (SDGs, listed in the Figure 1) to serve as a “shared blueprint for peace and prosperity for people and the planet” that were adopted into the UNGA’s 2030 Agenda, when most goals are to be achieved. Sustainable Development goal 3, (SDG3) is, “Good Health and Well-Being.”